2022
DOI: 10.3390/d14060452
|View full text |Cite
|
Sign up to set email alerts
|

The Bioconcentration and the Translocation of Heavy Metals in Recently Consumed Salicornia ramosissima J. Woods in Highly Contaminated Estuary Marshes and Its Food Risk

Abstract: Salicornia species are halophyte plants that are an important source for food, pharmacy, and bioenergy. They can be consumed as a leafy vegetable, but they can accumulate heavy metals that carry a health risk when knowledge of how each species behaves in different types of soil is lacking. This present work aimed to determine to what extent S. ramosissima can be cultivated as food in estuaries contaminated by heavy metals and to what extent it can be used in phytoremediation works, by studying its behavior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…However, with climate change, phenomena such as forest fires have intensified dramatically in Portugal, and a direct relationship has been documented between the mobilisation and accumulation of elements such as Hg, Mn, and Zn in ecosystems and the occurrence of these events [ 84 , 85 ], which could ultimately lead to a greater accumulation of these HMs in the species under study. Finally, as shown in the studies by Yang et al [ 86 ] and Sanjosé et al [ 72 ], in the case of specimens from highly contaminated areas, the risk of accumulation by HMs at levels that represent a health risk is real and should not be overlooked. Hence, the introduction of specific legislation for halophytes is a fundamental step to guarantee the safety of their consumption.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, with climate change, phenomena such as forest fires have intensified dramatically in Portugal, and a direct relationship has been documented between the mobilisation and accumulation of elements such as Hg, Mn, and Zn in ecosystems and the occurrence of these events [ 84 , 85 ], which could ultimately lead to a greater accumulation of these HMs in the species under study. Finally, as shown in the studies by Yang et al [ 86 ] and Sanjosé et al [ 72 ], in the case of specimens from highly contaminated areas, the risk of accumulation by HMs at levels that represent a health risk is real and should not be overlooked. Hence, the introduction of specific legislation for halophytes is a fundamental step to guarantee the safety of their consumption.…”
Section: Resultsmentioning
confidence: 96%
“…Barreira et al [ 12 ] also reported an important variation in the concentration of the different HMs in Salicornia and Sarcocornia species, even when differences in environmental factors were minimal. These differences may be related to factors such as, among others: (i) differences in the life cycle, as S. ramosissima is annual and S. perennis alpini is perennial, and as a consequence, the metabolic requirements for certain macronutrients and micronutrients at the time of harvest may differ; (ii) the presence of root exudates, which can improve the solubility of certain HMs and thus increase their accumulation [ 72 ]; and (iii) differences in the microbiome [ 73 ]. The order of HM concentrations determined in this study for S. ramosissima was Mn > Zn > Cr > Cu > Co > Ni > Cd > Pb > Hg, whilst that for S. perennis alpini was Mn > Zn > Ni > Cr > Cu > Co > Pb > Cd > Hg.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of Cd in stems was 0.08 ± 0.04 mg/kg and 0.06 ± 0.01 mg/kg for RM and GM but the difference between both treatments did not reach statistical significance ( p < 0.05), respectively, no accumulation was detected Cd in leaves. The Bioaccumulation Factor (BF) is defined as the correlation between the quantity of HMs accumulated in various plant components and the concentration of HMs in the soil (Sanjosé et al 2022 ), RM showed a BF of 1.79 for Pb. At the same time, GM exhibited a BF of 0.94.…”
Section: Resultsmentioning
confidence: 99%
“…However, caution is advised, as some authors recommend avoiding the use of the green stems of Salicornia species that grow in estuaries with high heavy metal content, such as those in the Tinto and Odiel Rivers [ 51 ]. Our ICP-MS analyses on succulent stems and inflorescences of Arthrocnemum align with these recommendations, revealing high contents of heavy metals such as Pb and Cr.…”
Section: Discussionmentioning
confidence: 99%